Optimising processing conditions of flax fabric reinforced Acrodur biocomposites. (November 2014) - Islam, MS; Miao, M
Acrodur solution and dispersion have been developed as alternative wood adhesives to phenolic and urea formaldehyde resins. They are non-corrosive and do not emit carcinogenic gases. Contrary to most resins used in natural plant fibre composites, Acrodur has superior tolerance to moisture during composite fabrication and thus drying of the preforms may be minimised or eliminated. The aim of this study was to produce optimised flax fabric reinforced Acrodur biocomposites by varying the ratio between Acrodur solution and dispersion, relative humidity, curing time and temperature. The optimised biocomposites provided a combination of specific tensile strength 57.9 MPa-cm 3 /g and specific Young's modulus 5.5 GPa-cm 3 /g at a low density 0.91 g/cm 3 . Thermogravimetric analysis and contact angle measurement showed that the biocomposites had higher thermal stability and hydrophobicity than the fabrics. The low loss of tensile properties upon water immersion was explained by tortuous wicking path in the biocomposites.